2015
DOI: 10.1038/jhh.2015.63
|View full text |Cite
|
Sign up to set email alerts
|

The hemodynamic patterns in hypertensive men and women of different age

Abstract: Aging is associated with cardiovascular remodeling, which can be accelerated in arterial hypertension (AH). The aim of this study was to evaluate the relation between hemodynamic profile and age, as well as to identify the role of sex in hemodynamic patterns of aging in AH. The study comprised 326 patients with AH (mean age: 44.3 years). Two-dimensional echocardiography was performed to evaluate, that is, left ventricular diastolic dysfunction (LVDD) and ejection fraction (LVEF), and ICG to evaluate, that is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…A previous study by Scuteri et al [ 46 ] found that increased aortic stiffness (a sign of reduced arterial compliance) is implicated in the age-associated rise in SBP and PP; such a finding was noticed in our patients with D-SDH and ISH subtypes (Table 1 ). Similar findings were also reported by Krzesinski et al employing impedance cardiography [ 31 ]. Instead, younger individuals showed a preserved C t and characteristically presented with IDH or ND-SDH subtypes (Table 1 ).…”
Section: Discussionsupporting
confidence: 91%
“…A previous study by Scuteri et al [ 46 ] found that increased aortic stiffness (a sign of reduced arterial compliance) is implicated in the age-associated rise in SBP and PP; such a finding was noticed in our patients with D-SDH and ISH subtypes (Table 1 ). Similar findings were also reported by Krzesinski et al employing impedance cardiography [ 31 ]. Instead, younger individuals showed a preserved C t and characteristically presented with IDH or ND-SDH subtypes (Table 1 ).…”
Section: Discussionsupporting
confidence: 91%
“…The results from this analysis support that E:IVRT values serve as a more reliable predictor of DD in rhesus macaques as opposed to LV‐IVRT alone; the authors suggest that E:IVRT may represent a second valuable index for assessment of diastology in rhesus macaques. Similar to human reports, rhesus macaque E/A measurements are negatively correlated with age and body weight 28,29 . Because our final MLR model could only explain 32.05% of Log_E/A values, there are likely other covariables that could drive a better model for predicating E/A in rhesus macaques that were not included in this study, therefore, an even more robust dataset is warranted for future studies.…”
Section: Discussionsupporting
confidence: 54%
“…28,29 Because our final MLR model could only explain 32.05% of Log_E/A values, there are likely other covariables that could drive a better model for predicating E/A in rhesus macaques that were not included in this study, therefore, an even more robust dataset is warranted for future studies. We report that SPF status is not a significant predictor for measures of diastology, thus, it is unlikely that a role for infectious disease (such as viral myocarditis secondary to common pathogens) in DD of rhesus macaques exist; we confirm that an index of exercise activity (housing configuration) is a notable variable when assessing diastology in rhesus macaques and should be considered in future cardiovascular study designs as increased exercise in the outdoor housing configuration imparts a reduced hazard ratio for diastolic dysfunction.…”
mentioning
confidence: 99%
“…The PEP, thoracic fluid content (TFC)a measure of preload, and cardiac output (CO) were recorded by impedance cardiography (CardioScreen ® 2000, Medis, Germany). Systemic vascular resistance (SVR) -a measure of afterload -was calculated as a ratio of mean arterial pressure and CO, assuming zero venous pressure at the right atrium (Krzesiński et al 2012, Krzesiński et al 2016, Lasater and Von Rueden 2003, Sodolski and Kutarski 2007, Xiajuan et al 2013. The duration of the PEP was defined as the time interval between R peak of the ECG and the B point of dZ/dt of the ICG and TFC was calculated from the base impedance Z 0 (TFC=1,000/Z 0 ).…”
Section: Data Acquisitionmentioning
confidence: 99%